اعتماد برنامج المکتبات والمعلومات بجامعة المنوفية : المشکلات والصعوبات - فاطمة خمیس (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to identify the problems and difficulties that the Librariesand Information Department faced when applying the standards, indicators,elements and characteristics of the evaluation and accreditation guide for theeducational program in higher education institutions and Al-Azhar through theexperience of accrediting the Library and Information Program at the University ofMenoufia.The study identified problems at the level of five main axes focused Thefirst axis focused on problems from a formal point of view, while the second axisdealt with coding at the level of standards, while the third axis represented theabsence of forms for questionnaires required for accreditation, while the fourthaxis devoted to problems at the level of procedures, and finally the fifth axisaddressed problems at the level of relationships between standards, Theresearcher used the Descriptive Analytical Methodology, as the researcheranalyzed the actual content of the actual application of the evaluation andaccreditation guide for the educational program in higher education institutionsand Al-Azhar through the experience of accrediting the library and informationprogram at the University of Menoufia , The study reached to identify thoseproblems in the above five axes, the most important of which are the presence ofindicators, elements and characteristics in other than their correct locations, therecurrence of coding at the level of the first three criteria under each of theprogram management axis and the axis of educational effectiveness, theabsence of models of questionnaires required to meet the criteria , The guidedoes not include flowcharts in which the starting point and the end point arespecified to meet the standard, the absence of a model procedural guide thatclarifies the steps of work within the standard and one of the most importantrecommendations of the study is the preparation of a model procedural guide bythe National Authority to ensure the quality of education and accreditationclarifies the method of work within Evaluation and accreditation guide for the  educational program in higher education institutions and Al-Azhar, preparing anew edition of the "evaluation and accreditation guide for the educationalprogram in higher education and Al-Azhar institutions taking into account thefollowing: Non-repetition of coding at the level of the first three criteria under boththe program management axis and the educational effectiveness axis and toinclude The new version of the guide provides flow charts that define a point Thestart and the end point to meet the standard